Pengelolaan Program Ekstrakurikuler di UPTD Sekolah DasarNegeri 05 Sarilamak Kecamatan Harau Kabupaten Lima Puluh Kota - Zulfikar Ayatulloh; Suswati Hendriani (Warta Pendidikan | e-Journal, 2023)
This study aims to find out (1) Planning for extracurricular activities at UPTD SDN Sarilamak Harau Regency, (2) Implementation of extracurricular activities at UPTD SDN 05 Sarilamak Harau District, (3) Implementation of extracurricular activities at UPTD SDN 05 Sarilamak Harau District, (4) Evaluation extracurricular activities at UPTD SDN 05 Sarilamak, Harau District, and (5) Inhibiting factors for extracurricular activities at UPTD SDN 05 Sarilamak, Harau District. This study uses a qualitative approach using descriptive methods. Data collection techniques in this study through observation, interviews, making field notes, observation, and documentation. Procedure data analysis using a qualitative descriptive analysis strategy model and a qualitative verification analysis strategy model. Based on the results of the study it can be concluded that (1) In designing extracurricular activities the principal holds a joint meeting with the teacher and the committee, then the principal makes a decision letter which is shown to the teacher who is given the assignment. become extracurricular coaches who do have expertise in the extracurricular field and give authority to create program activities, (2) the principal together with the extracurricular supervising teacher create a management structure which is led directly by the principal and assisted by other teachers as executors of supervisory activities, (3 ) the implementation of these extracurricular activities is carried out in the school yard by involving all students who choose the extracurricular activities they like, (4) In the evaluation the principal assesses the extracurricular results in the form of personality possessed by students and achievements achieved by students as a result of their participation in extracurricular activities, and (5 ) The service factor for extracurricular activities includes the low motivation of students to participate in extracurricular activities and the low support of parents for children to participate in these activities.